Pengaruh Variasi Waktu Gesek Pada Pengelasan Gesek (Friction Welding) Terhadap Kekuatan Impak Baja AISI 1045 Dengan Stainless Steel - Pranata, Syendy; Sugiyarto, Sugiyarto; Erwanto, Erwanto (Politeknik Manufaktur Negeri Bangka Belitung, 2023)
The Friction Welding method is a welding method that utilizes heat energy caused by the friction of the two materials to be joined, the heat from the friction will cause the material to become semisolid or plastic. The purpose of this research was to determine the effect of variations in friction time and distance suppression carried out on impact strength and hardness tests using the Friction Welding method on AISI 1045 steel material connected to Stainless Steel 304. The method used is the Response Surface Method (RSM) to determine impact strength value of AISI 1045 steel which is connected to Stainless Steel 304 after the friction welding process is carried out. The variation used in this study is the variation of the pressure distance and friction time. The size of the impact test specimen is made according to the impact test standard, namely ASTM E23. The greatest impact test results were found in specimen number 6 with a pressing distance of 4.41 mm and a friction time of 5 minutes, namely 0.156 Joule/mm2. While the lowest impact value is found in specimen number 1 with a pressing distance of 2 mm and a friction time of 4 minutes, namely 0.038 Joule/mm2.